Key factors for reengineering local construction firms towards successful overseas ventures - Chua, Hin Bee. (2009)
It is becoming increasingly difficult to manage an international construction business in today's environment. This is due to changes brought about by the emergence of new markets, the diminishing or shrinking of existing markets, of new opportunities arising, and of changing business cycles and intense competition.